The Development of Mathematics Learning Management Model Linked to Life Style for Grade 4 - 6 Student at Ban Non Chan School - Noyjun, Emnikar; sasanatorn, Prakhruvitit; Pakdee, Chalee (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
This research aimed to: 1. study the management of mathematics learning connected to real-life contexts; 2. develop a model for mathematics learning management; 3. implement the model; and 4. evaluate the model. The research instruments included a model process evaluation form and a satisfaction evaluation form, administered to a sample group consisting of 12 school administrators and teachers. Data were analyzed using a paired sample t-test. The research findings revealed that Nonchan School demonstrated systematic management practices but lacked opportunities for parental involvement. Teacher development was emphasized through enhancing learning management skills that link mathematics to real-life contexts. The model, synthesized through expert group discussions, comprised four components: 1. linking prior knowledge to new knowledge; 2. constructing knowledge through experience; 3. collaborative learning; and 4. application of knowledge. The model was tested through pre- and post-implementation assessments across four stages and 13 indicators. Among the evaluated aspects, using questions to connect prior knowledge had the highest mean score (M = 3.87), followed by motivational game activities (M = 3.79), while the presentation of thought processes and outcomes received the lowest score (M = 3.12). The satisfaction evaluation indicated a high level of satisfaction overall (M = 4.04). The highest-rated aspect was the appropriateness of the model for practical application (M = 4.64), followed by clarity and suitability of each step (M = 4.46), and clarity and engagement of activities (M = 4.18). The aspect with the lowest mean score was the appropriateness of difficulty and ease (M = 3.52), which was still rated at a high level.